2012
DOI: 10.1111/j.1600-0501.2012.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Single unit attachments improve peri‐implant soft tissue conditions in mandibular overdentures supported by four implants

Abstract: Although the patients' satisfaction was similar in both groups the Locator(®) system demonstrated better soft tissues scores because hygienic maintenance was more complicated around bars. This may increase the frequency of chronic inflammations around the implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
(57 reference statements)
3
38
0
2
Order By: Relevance
“…In the last decade, a new self-aligning attachment system (Locator ® ; Zest Anchors LLC, Escondido, CA, USA) for implantretained OD has seen an increasing popularity. Several recent studies have concluded that the Locator system showed equal or superior clinical results than the ball and the bar attachments, with regard to the rate of prosthodontic complications and the maintenance of the oral function (Kleis et al 2010;Bilhan et al 2011b;Cakarer et al 2011;Mackie et al 2011;Cordaro et al 2012). Nevertheless, none of the included studies in this review presented data including the use of this type of tool.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the last decade, a new self-aligning attachment system (Locator ® ; Zest Anchors LLC, Escondido, CA, USA) for implantretained OD has seen an increasing popularity. Several recent studies have concluded that the Locator system showed equal or superior clinical results than the ball and the bar attachments, with regard to the rate of prosthodontic complications and the maintenance of the oral function (Kleis et al 2010;Bilhan et al 2011b;Cakarer et al 2011;Mackie et al 2011;Cordaro et al 2012). Nevertheless, none of the included studies in this review presented data including the use of this type of tool.…”
Section: Discussionmentioning
confidence: 87%
“…This continuity correction is the default in the “metan” command in Stata as in RevMan, the software used by the Cochrane Collaboration (Deeks et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Maniewicz et al 27 The increased plaque and gingival scores may be attributed to the increased tendency for food and plaque accumulation within the recess of the matrix abutment with the Locator attachment. 28 In contrast, other authors 26,29 found that these parameters did not significantly change with time when Locator attachments were used. This may be because participants in these studies underwent strict oral hygiene procedures, while the majority…”
Section: Discussionmentioning
confidence: 89%
“…Although, the search strategy was broadened possible eligible publications (Larsson & Vult von Steyern 2010;Larsson & Vult Von Steyern 2013)which the authors were aware ofwere missed. While scrutinizing these two papers, the authors realized that the search terms that have been applied were Jemt et al (1999) Sample size per study arm Balshi et al (2012) Study design Becker et al (2000) No characteristics on restorations Borges et al (2012) No characteristics on restorations Ericsson et al (2000) No characteristics on restorations Di Giacomo et al (2012) Sample size/study design € Ortorp & Jemt (2000) Interim results of included study Ercoli et al (2012) Study design/sample size € Ortorp & Jemt (2002) Interim results of included study Furze et al (2012) Sample size Henriksson & Jemt (2003) Sample size per study arm Giordano et al (2012) Sample size Romeo et al (2003) Study design/no CAD/CAM prostheses Meloni et al (2012) Quality of reporting Engquist et al (2004) Follow-up, study design Tahmaseb et al (2012) No characteristics on restorations/follow-up € Ortorp & Jemt (2004) Interim results of included study Biscaro et al (2013) Sample size van Steenberghe et al (2005) Study design/no CAD/CAM restorations Lin et al (2013) No characteristics on restorations Gallucci et al (2007) Sample size/study design Cordaro et al (2013) No characteristics on restorations Malo et al (2007) Study design/sample size Kanao et al (2013) No characteristics on restorations/sample size Sanna et al (2007) No characteristics on prostheses Katsoulis et al (2013) No response/quality of reporting Vafiadis (2007) Case report/study design (2010) Sample size/study design Alfadda (2014) In vitro design…”
Section: Discussionmentioning
confidence: 99%